Soundbites on COVID-19 and One Health work by the CGIAR research programs on A4NH and Livestock - Randolph, Thomas F.; McDermott, John J. (International Livestock Research Institute, 2020)
In this video, John McDermott, director of the CGIAR Research program on Agriculture for Nutrition and Health, and Thomas Randolph, director of the CGIAR Research Program on Livestock Agri-Food Systems, share summaries of the joint work in COVID-19 and One Health research being carried out by the two programs.